Prince & Pirate - Gunnufson, Charlotte; Lowery, Mike, 1980- (New York, NY : G.P. Putnam's Sons, 2017)
"When a pirate fish and a prince fish are dropped into the same fishtank, it doesn't seem like they'll ever get along--until the arrival of a third fish inspires them to cooperate"--
Keywords: Aquarium fishes -- Juvenile fiction; Fishes -- Juvenile fiction; Aquariums -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Princes -- Juvenile fiction; Pirates -- Juvenile fiction; Aquarium fishes -- Fiction; Fishes -- Fiction; Aquariums -- Fiction; Cooperativeness -- Fiction; Princes -- Fiction; Pirates -- Fiction